2000
DOI: 10.1007/s002670010107
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Aquatic Plant Community Biotic Index for Wisconsin Lakes

Abstract: The Aquatic Macrophyte Community Index (AMCI) is a multipurpose tool developed to assess the biological quality of aquatic plant communities in lakes. It can be used to specifically analyze aquatic plant communities or as part of a multimetric system to assess overall lake quality for regulatory, planning, management, educational, or research purposes. The components of the index are maximum depth of plant growth; percentage of the littoral zone vegetated; Simpson's diversity index; the relative frequencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 11 publications
0
38
0
2
Order By: Relevance
“…Nichols et al (2000) found that the vegetation responses to environmental factors are not always linear. While Jones et al (2003) did not find any relationships between nitrate and phosphorus concentrations and the diversity of aquatic plants in ponds, Rørslett (1991) and Murphy (2002) found that the highest macrophyte diversity was observed in mesotrophic or slightly eutrophic lakes.…”
Section: Discussionmentioning
confidence: 97%
“…Nichols et al (2000) found that the vegetation responses to environmental factors are not always linear. While Jones et al (2003) did not find any relationships between nitrate and phosphorus concentrations and the diversity of aquatic plants in ponds, Rørslett (1991) and Murphy (2002) found that the highest macrophyte diversity was observed in mesotrophic or slightly eutrophic lakes.…”
Section: Discussionmentioning
confidence: 97%
“…As they are non-mobile and cannot flee from rapid environmental changes (Clayton & Edwards, 2006), SAV provides a mechanism for relating anthropogenic inputs to the health of the UMRS. As a result, SAV can reflect both the long-term trends and short-term episodes within the watershed (Nichols et al, 2000) and can serve as a potential biological indicator of turbidity, nutrient enrichment, and other water quality impairments. Aquatic vegetation indices are currently being developed for the upper impounded reach of the UMRS as an indicator of system health (Langrehr & Moore, 2008).…”
Section: Biological Indicatorsmentioning
confidence: 99%
“…Nichols et al (2000) proposed an aquatic plant community biotic index for Wisconsin lakes, and Rothrock et al (2008) proposed a plant index of biotic integrity for lacustrine wetlands in northwest Indiana, but neither of these indices was directly related to the anthropogenic loading of plant nutrients. Likewise, Beck et al (2010) discussed the development of a macrophyte-based index of biotic integrity for Minnesota lakes.…”
Section: Introductionmentioning
confidence: 99%